Radial growth and climatic influences on Greek fir: Tree ring analysis from Kirphi mountain, Central Greece - Koulelis Panagiotis P.; Solomou Alexandra; Fassouli Vassilia; Petrakis Panos V.; Spanos Ioannis (Folia Oecologica, 2025)
In the era of global climate fluctuations, understanding the intricate relationship between trees and climatic factors is crucial for assessing ecosystem resilience and adapting to environmental changes. This study explores the radial growth of Greek fir (Abies cephalonica) in response to climatic factors in Kirphis mountain, Central Greece. The plants diversity of the area makes Kirphi one of the most crucial reserves for endemic flora, necessitating focused conservation efforts for its preservation. Using detailed tree ring analysis, gridded climate data, and data from nearby meteorological stations, we investigated how climatic variables influence fir growth dynamics. Despite the moderate climate signal observed, οur findings highlight the sensitivity of fir growth to climatic variability, with significant correlations identified between tree-ring width and drought indices. Drought conditions, measured by SPI-12 and PDSI-12, significantly affect fir ring growth. The strongest correlation was observed with SPI-12, indicating that long-term precipitation patterns play a key role. A lower correlation with evapotranspiration suggests adaptation to droughts, while the positive link with annual precipitation shows water availability is important but not the only factor. Ultimately, this research may provide valuable insights into the adaptive strategies of Greek fir forests in response to climatic fluctuations, potentially informing conservation and management practices in Mediterranean mountain ecosystems.